1986
DOI: 10.1007/bf01648345
|View full text |Cite
|
Sign up to set email alerts
|

Rectal manifestations of pellagra

Abstract: Twenty (44%) of 45 patients with cutaneous pellagra had diarrhoea. Inflammation was seen on sigmoidoscopy in 42 and was severe in 5 (11%), moderate in 4 (9%) and mild in 33 (73%). Six patients (13%) had perianal excoriation. Rectal biopsies taken in all cases showed extensive ulceration in 1 case, moderate to severe inflammation in 16 (36%) and mild inflammation in 18 (40%). Minimal oedema of the lamina propria was seen in 11 (24%) patients. At 5 to 7 days after starting vitamin treatment in nine cases histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…The diarrhoea was associated with inflammation of both the large and the small intestine. The most marked changes were seen in the colon and rectum, and the biopsy appearances were similar to those previously described in dietary pellagra [12]. The patient's psychological changes were also compatible with a diagnosis of pellagra, in which the encephalopathy usually takes the form of a psychosis.…”
Section: Discussionsupporting
confidence: 54%
“…The diarrhoea was associated with inflammation of both the large and the small intestine. The most marked changes were seen in the colon and rectum, and the biopsy appearances were similar to those previously described in dietary pellagra [12]. The patient's psychological changes were also compatible with a diagnosis of pellagra, in which the encephalopathy usually takes the form of a psychosis.…”
Section: Discussionsupporting
confidence: 54%
“…Colitis, which is histologically similar to ulcerative colitis, has also been described in association with pellagra. 5 How the various forms of nutritional colitis relate to ulcerative colitis (UC) is uncertain, but studies have suggested that metabolism of the short chain fatty acid butyrate is impaired in UC.i In these studies, in common with many others, it has not been possible to discover if the change was a primary defect or merely a secondary effect of the disease process.…”
mentioning
confidence: 99%
“…Interestingly, inflammatory diseases of the gut are frequently associated with deficiencies of certain water‐soluble vitamins. For example, 90% of patients with pellagra, who have vitamin B 6 deficiency, suffer from colitis . Biotin regulates activity of natural killer cells, which is reduced, along with systemic biotin levels, in patients with Crohn's disease .…”
Section: Impact On the Innate Immune Systemmentioning
confidence: 99%